2019
DOI: 10.31989/ffhd.v9i2.548
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Pharmacokinetic Evaluation of a Bioavailable Curcumin Formulation Curene® with Curcumin Formulation Containing Turmeric Volatile Oil and Standard Curcuminoids 95% in Healthy Human Subjects

Abstract: Background: Curcumin, a major active component of turmeric, which is one of the most studied botanicals for its numerous health benefits and higher safety profile. In spite of its potent clinical health benefits, its applications are circumscribed due to its poor bioavailability. The current study was carried out to compare the oral bioavailbility of newly developed bioavailable curcumin formulation Curene® with Curcumin formulation containing turmeric volatile oil (CP-01) and Standard Curcuminoids 95% in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A study was conducted to compare the oral bioavailability of the newly developed formulation of curcumin Curene ® with a formulation of curcumin containing volatile turmeric oil (CP-01) and standard curcuminoids 95%, on healthy volunteers. It was found that the oral bioavailability of Curene ® is significantly higher compared with CP-01 and standard curcuminoids (95%) and that it is safe to be administered to healthy people in trial conditions [ 136 ]. The anti-inflammatory activity of Longvida ® Optimized Curcumin (LC) was examined on two-month-old wild-type mice and GFAP-IL6.…”
Section: Formulationsmentioning
confidence: 99%
“…A study was conducted to compare the oral bioavailability of the newly developed formulation of curcumin Curene ® with a formulation of curcumin containing volatile turmeric oil (CP-01) and standard curcuminoids 95%, on healthy volunteers. It was found that the oral bioavailability of Curene ® is significantly higher compared with CP-01 and standard curcuminoids (95%) and that it is safe to be administered to healthy people in trial conditions [ 136 ]. The anti-inflammatory activity of Longvida ® Optimized Curcumin (LC) was examined on two-month-old wild-type mice and GFAP-IL6.…”
Section: Formulationsmentioning
confidence: 99%